Assessing quality and distribution of surface runoff and soil from a mixed-use catchment, Teluk Intan in Malaysia - Lye Xin Yan; Nakayama Akihiko (E3S Web of Conferences)
Surface water quality of river channels has been well examined over the years, without much focus on one of the potential contributors, that is surface runoff transporting contaminants from surrounding land. By analysing the amount of contaminants present in surface runoff and soil on the ground, the potential extent of contamination can be examined in addition to the influence of different land use. The quality of surface runoff and soil from a mixed-use catchment in Teluk Intan, Malaysia was investigated for one storm event in 2023. A total of 10 points along a main road were sampled for surface runoff and soil, both of which were analysed for Total Kjeldahl Nitrogen (TKN) and lead (Pb). Both parameters concluded a higher concentration in soil compared to runoff, indicating transport across different medias. TKN was measured at a maximum of 0.0911% in runoff and 0.473% in soil. The highest Pb concentrations of 0.423 mg/L for runoff and 66.48 mg/kg for soil were recorded at the points near the Perak River bend, which is in line with Smoothed Particle Hydrodynamics (SPH) simulation results. According to the National Water Quality Standard (NWQS), the Pb concentration in runoff was beyond the Class III limit. Herein, surface runoff exhibits a significant role in contaminant transport along the observed main road and poses a risk of entry into the Perak River. The present analysis may benefit as an estimation or comparison of typical runoff pollutant loading to improve the environmental quality of similarly mixed urban-agricultural catchment in Malaysia.